Distrust or speculation? - Auer, Raphael A.,Tercero-Lucas, David (CESifo, Center for Economic Studies & Ifo Institute, 2021)
Employing representative data from the U.S. Survey of Consumer Payment Choice, we disprove the hypothesis that cryptocurrency investors are motivated by distrust in fiat currencies or regulated finance. Compared with the general population, investors show no differences in their level of security concerns with either cash or commercial banking services. We find that cryptocurrency investors tend to be educated, young and digital natives. In recent years, a gap in ownership of cryptocurrencies across genders has emerged. We examine how investor characteristics vary across cryptocurrencies and show that owners of cryptocurrencies increasingly tend to hold their investment for longer periods.
10419/245468
Keywords: Graue Literatur; digital currencies; cryptocurrencies; distributed ledger technology; blockchain; payments; digitalisation; banking; household finance; money; bitcoin; ether; xrp; bitcoin cash; litecoin; stellar; eos